2021
DOI: 10.1186/s12992-021-00678-4
|View full text |Cite
|
Sign up to set email alerts
|

Countries with delayed COVID-19 introduction – characteristics, drivers, gaps, and opportunities

Abstract: Background Three months after the first reported cases, COVID-19 had spread to nearly 90% of World Health Organization (WHO) member states and only 24 countries had not reported cases as of 30 March 2020. This analysis aimed to 1) assess characteristics, capability to detect and monitor COVID-19, and disease control measures in these 24 countries, 2) understand potential factors for the reported delayed COVID-19 introduction, and 3) identify gaps and opportunities for outbreak preparedness, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 25 publications
1
24
0
1
Order By: Relevance
“…This result could help the authorities to implement the necessary measures to more effectively control the upcoming surge of cases and protect public health. Previous research showed that a common characteristic among countries with delayed onset was the implementation of effective border measures and various preparedness activities at an early stage (Kousi et al, 2020;Li et al, 2021;Ayouni et al, 2021). Conversely, countries that had a higher value of preparedness index were among the first ones in which the outbreak initiated.…”
Section: Major Findings and Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result could help the authorities to implement the necessary measures to more effectively control the upcoming surge of cases and protect public health. Previous research showed that a common characteristic among countries with delayed onset was the implementation of effective border measures and various preparedness activities at an early stage (Kousi et al, 2020;Li et al, 2021;Ayouni et al, 2021). Conversely, countries that had a higher value of preparedness index were among the first ones in which the outbreak initiated.…”
Section: Major Findings and Trendsmentioning
confidence: 99%
“…Perhaps, countries better prepared to control an epidemic had also enhanced testing capabilities, and as a result were able to detect and identify cases earlier. Indeed, a study focusing on the 24 SSA countries that were COVID-19 free as of March 30, 2020 documented that only 38% of them had COVID-19 testing capacities (Li et al, 2021). Although we found that stringent policies are helpful in controlling the pandemic, many of these measures were associated with other negative consequences (Katana et al, 2021;Bourgault et al, 2021).…”
Section: Major Findings and Trendsmentioning
confidence: 99%
“…Other researchers look at growth rates of cases or estimates of R t , calculated in various ways. Some studies use the date of the first recorded case, or the 100th case, as the “beginning” of the pandemic in a country (or conversely, focus on countries not reporting a case by a certain date [ 15 ]). Others focus on hospitalized cases, or hospital capacity.…”
Section: Main Textmentioning
confidence: 99%
“…Conversely, although no o cial temporary housing solution was available, the British government provided advice for citizens without accommodation and encouraged speaking to the local British consulate or high commission for further advice. 4. Support and information available for citizen/traveller registration Overall, 9/11 countries examined provided a form of registration focused on supporting citizens abroad, whether through information sharing, alerts, or the ability for local consulate support (see Table 2).…”
Section: Emergency Housingmentioning
confidence: 99%
“…In response to the threats posed by the COVID-19 pandemic, countries around the world have imposed some level of international travel restriction for returning travellers (1)(2)(3). Border restriction (or closure) was one of the earlier and most common non-pharmaceutical interventions implemented, with countries -including Australia, Italy, the Paci c Island countries and territories, and the USA-imposing some form of travel restrictions as early as February 2020 (1,4). Restrictions included suspending (or limiting) the number of international ights, suspending visa free travel as well as the use of enhanced quarantine and screening measures, and the issuing of recommendations to avoid non-essential travel (1)(2)(3)5).…”
Section: Introductionmentioning
confidence: 99%